Development of Ethnomathematics-Based Student Worksheets on Course of Mathematics Basic Concept in STKIP Singkawang - Evinna Cinda Hendriana; Buyung Buyung (JETL (Journal of Education, Teaching and Learning), 2020)
The success of learning mathematics affects the level of mastery of mathematical concepts that elementary school students (SD) must have, as well as prospective elementary school teachers at STKIP Singkawang. One of the factors that support the success of learning mathematics is a model of teaching materials in the form of systematic student worksheets (LKM) and interesting so that it is easy for students to learn individually. The purpose of researching the Development of Ethnomathematics-Based Student Worksheets in the course of Mathematics Basic Concept at STKIP Singkawang is valid, practical, and effective. The method used in this research is the development of the Borg and Gall (1979) 3D model, namely: define, design, and develop. The research subjects were 2 classes, namely the morning class (class A and class B) of the PGSD study program of STKIP Singkawang. Data analysis in this study was carried out through qualitative analysis and quantitative analysis. The quantitative analysis conducted in this study includes validity analysis, practicality analysis, effectiveness analysis. Statistical test using the t-test, Z-test, and ANOVA test. The results showed that the learning tools developed were: (1) valid, after going through the validation process, (2) practical, because there was a good response from students, and (3) the ethnomathematics -based LKM learning tools were effective because the students' ability to understand mathematical concepts reached individual and classical completeness, as well as differences in the ability to understand mathematical concepts in the two classes of device trials.